IMPLEMENTASI Al-MASYAQQOH Al-TAJLIBU Al-TAISYIIR DI TENGAH PANDEMI COVID-19 - Sahari Sahari (Aqlam: Journal of Islam and Plurality, 2020)
Abstrac: The purpose of this study is to explain the meaning of “al-masyaqqoh al-tajlibu al-taisyiir”, the implementation of these principles during the Covid-19, to find out the understanding of the Manado people about these principles and finally to describe the response of the Manado Muslim community to the MUI fatwas, especially Friday prayers. 'at the time of the Covid-19 pandemic. The research used an exploratory case study method and the research approach was qualitative. The informants who were interviewed were 15 people from 5 mosques consisting of imams, ta'mir, and congregation of mosques, interviews were conducted by telephone, because they were worried about contracting the virus when interviewing face to face. Research results: People are still not familiar with the rules of al-masyaqqoh al-tajlibu al-taisyiir, what they know is the term 'emergency', but the term emergency is too narrow and has very limited meaning, which is only limited to life-threatening things that result. by the absence of food. In practice, al-masyaqqah must be adapted to the conditions and situations, at least there are two conditions, namely al-masyaqqah al-'Azhimmah, and al-masyaqqah al-Khafifah. Regarding the MUI fatwa, there are agree and disagree in the community, some have responded positively and some have refused.Key words: Understanding, Perception, Al-Masyaqqoh Al-Tajlibu Al-Taisyiir, MUI Fatwa, Covid-19 Pandemic. Abstrak:Tujuan dari penelitian ini adalah untuk menjelaskan makna al-masyaqqoh al-tajlibu al-taisyiir, implementasi kaedah tersebut pada masa pandemi covid-19, mengetahui pemahaman masyarakat Manado tentang kaedah tersebut dan yang terakhir  untuk mendeskripsikan respon masyakat muslim Manado terhadap fatwa MUI khususnya shalat jum’at di masa pendemi covid-19. Penelitian menggunakan metode studi kasus eksplorasi dan pendekatan penelitiannya menggunakan kualitatif. Informan yang diwawancarai sebanyak 15 orang dari 5 mesjid terdiri dari imam, ta’mir, dan jama’ah masjid, wawancara dilakukan melalui telepon, pertimbangannya karena kekhawatiran terjangkit virus apabila wawancara dengan tatap muka. Hasil penelitian:  Masyarakat masih belum mengenal kaedah al-masyaqqoh al-tajlibu al-taisyiir, yang mereka tau adalah istilah ‘darurat’, tetapi istilah darurat pun terlalu sempit dan sangat terbatas dimaknainya, yaitu hanya terbatas pada hal-hal yang mengancam jiwa yang diakibatkan oleh ketiadaan makanan. Dalam prakteknya, al-masyaqqah harus disesuaiakan dengan kondisi dan situasi, minimal ada dua keadaan yakni al-masyaqqah al-‘Azhimmah, dan al-masyaqqah al-Khafifah. Terkait dengan fatwa MUI terjadi pro dan kontra di masyarakat ada yang menanggapi positif dan ada yang menolak.Kata Kunci: Pemahaman, Persepsi, Al-Masyaqqoh Al-Tajlibu Al-Taisyiir, Fatwa MUI, Pandemi Covid-19.